Integrative analysis of metabolome and transcriptome reveals regulatory mechanisms of flavonoid biosynthesis in soybean under salt stress - Wang, Yubin; Liu, Wei; Li, Wei; Wang, Caijie; Dai, Haiying; Xu, Ran; Zhang, Yanwei; Zhang, Lifeng (Frontiers in Plant Science, 2024)
Salt stress is a major environmental factor that constrains soybean growth, development, and productivity. Flavonoids are key secondary metabolites that play a crucial role in enhancing plant resistance to both biotic and abiotic stress. However, a comprehensive understanding of the regulatory mechanisms underlying flavonoid biosynthesis under salt stress in soybean is lacking.In this study, an integrative analysis of soybean metabolome and transcriptome was conducted using two soybean lines, FQ03 (salt-sensitive, SS) and FQ07 (salt-tolerant, ST). A total of 650 significantly changed metabolites were identified in SS and ST after salt stress treatment. Among them, 151 flavonoids were categorized into nine classes, with flavones and flavonols being the predominant flavonoid types in soybean. Heatmap analysis showed higher contents of most flavonoid metabolites in ST than in SS under salt stress, and the total flavonoid content in ST was significantly higher than that in SS. In addition, transcriptome analysis revealed a higher number of differentially expressed genes (DEGs) in ST than in SS under salt stress. KEGG enrichment analysis revealed that DEGs were mainly enriched in pathways related to phenylpropanoid biosynthesis, isoflavonoid biosynthesis, flavonoid biosynthesis, as well as flavone and flavonol biosynthesis. Notably, 55 DEGs that were mapped to the flavonoid biosynthetic pathway were identified, with most showing higher expression levels in ST than in SS. Weighted gene correlation network analysis identified eight structural genes and six transcription factor genes as key regulators of flavonoid biosynthesis within the blue module. Furthermore, qRT-PCR results confirmed the accuracy of the transcriptomic data and reliability of the identified candidate genes.This study provides insights into the regulatory mechanisms underlying salt stress responses in soybean and highlights hub genes as potential targets for developing salt-tolerant soybean varieties.